Determination of the degree of crystallinity of semicrystalline polymers by means of the "OptiFit" computer software - Rabiej, M. (Polimery, 2022)
A description of the ’’OptiFit" software used for resolution of X-ray diffraction patterns of semicrystalline polymers into components coming from crystalline and amorphous phases to calculate their degree of crystallinity (SK) has been given. The software implements the Hindeleh and Johnson procedure (also described in detail) and allows selection of one of four optimization methods. The software was applied to determine SK values of PET, PP and PA6 base don registration of their diffractograms.